EVALUASI KAPASITAS STRUKTUR EKSISTING LANTAI JEMBATAN PADA JEMBATAN TYPE PILE SLAB DI RUAS JALAN TOL JORR W1 KEBON JERUK - Fianda Harsa; Andi Indianto; Erlina Yanuarini (Construction and Material Journal, 2023)
This research a study transverse cracking that occurred on the floor structure of the pile slab type bridge located at JORR W1 Kebon Jeruk toll road. The purpose of this study was to evaluate the capacity of the bridge floor structure that had damaged by cracks and weather its remains are in a safe condition or not. The research method is carried out by analyzing the calculation of loading that occurred in an actual condition that had cracked by modeling on structural analysis program with standard SNI 1725:2016 and actual loads that acted on the structure, then evaluating the moment capacity of the structure based on installed reinforcement and evaluating deflection from inspection results based permissible deflection. From the results of the analysis, it was found that the structure experienced a moment failure due to the actual load with a load magnitude of 18,07 tons, the moment due to the actual load on the negative moment region was 34,47 tons.m and the positive moment region was 37,46 tons.m, compared to the moment capacity of structure successively which was 25,52 tons.m and 29,16 tons.m. However, for the results of the analysis of the standard load of 11,25 tons, the moment capacity of the structure was able to withstand the ultimate moment due to the reactor load successively being 22,82 tons.m and 24,37 tons.m, whereas for the deflection test results of 0,46 mm remained in a safe condition without exceeding the L/800 permit deflection of 4,76 mm. Based on the results of the analysis, it can be concluded that the structure is overloaded and in the future, the structural ability must be improved and it is necessary to strengthen the bridge floor structure to be able to increase the capacity of the structure so that it can withstand the working load.